1996
DOI: 10.1046/j.1365-3156.1996.d01-13.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of chloroquine, amodiaquine and pyrimethamine‐sulphadoxine in Gambian children with uncomplicated malaria

Abstract: SummaryThe increasing occurrence of chloroquine-resistant Plasmodium falciparum in sub-Saharan Africa makes it essential to reconsider current recommendations for the treatment of uncornplicated P. falciparum malaria. In an open, randomized trial, we have compared chloroquine (CQ), amodiaquine (AQ), and pyrimethamine-sulphadoxine (PS) in rural Gambian children with uncomplicated P. falciparum malaria. Three hundred children were randomly assigned at the time of consultation (Do) to oral treatment with 25 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 17 publications
5
40
1
2
Order By: Relevance
“…A similar level of resistance to SP was reported in Cameroon in 1997 and 1999 (30). Indeed, Central Africa seems to exhibit an intermediate prevalence of resistance to SP, between East Africa, where the resistance rate is around 30% in Uganda, Kenya, and Tanzania (18,19,22), and West Africa, where the rate of resistance remains lower, in the 0 to 10% range (5,21). Our study revealed a worsening of the treatment efficacy of AQ, with more than 30% treatment failures.…”
Section: Discussionsupporting
confidence: 66%
“…A similar level of resistance to SP was reported in Cameroon in 1997 and 1999 (30). Indeed, Central Africa seems to exhibit an intermediate prevalence of resistance to SP, between East Africa, where the resistance rate is around 30% in Uganda, Kenya, and Tanzania (18,19,22), and West Africa, where the rate of resistance remains lower, in the 0 to 10% range (5,21). Our study revealed a worsening of the treatment efficacy of AQ, with more than 30% treatment failures.…”
Section: Discussionsupporting
confidence: 66%
“…The relatively slow fever recovery effect by SP treatment alone confirms previous similar preliminary findings. 3 However, the anti-parasitic effect brings about a reduction of fever during the second day, but an antipyretic drug is still required up to 48 hours if clearance of fever is to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…3 An optimal treatment regimen may therefore be to combine SP and chloroquine, thus optimizing both the anti-parasitic and clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence of an increase in the prevalence of CQ-resistant parasites in the last decade, [1][2][3] and in neighboring Senegal, an increase in the number of CQresistant infections has been associated with increased child mortality. 4 It is crucial that the frequency of failures with CQ treatment is monitored carefully, since a change in malaria treatment policy may soon become necessary in The Gambia and other west African countries.…”
Section: Introductionmentioning
confidence: 99%